Vertical and horizontal distributions of coral‐reef fish larvae in open water immediately prior to reef colonization. Issue 6 (13th May 2013) - Lecchini, D.; Waqalevu, V. P.; Holles, S.; Lerohellec, M.; Brie, C.; Simpson, S. D.
<x xml:space="preserve">Abstract</x> To explore the vertical and horizontal distributions of fish larvae near the end of their pelagic period, six light traps were set up over four lunar months at different depths (sub‐surface, midwater and bottom) and different habitat types (reef slope: 50 m horizontal distance from the reef crest; frontier zone: 110 m horizontal distance; sandy zone: 200 m horizontal distance) on the outer reef slope of Moorea Island, French Polynesia. The highest captures were in sub‐surface traps on the reef slope and the frontier zone, and in bottom traps on the sandy zone and the frontier zone. It is hypothesized that fish larvae move towards the surface near the reef slope to avoid reef‐based planktivores and to get into a favourable position for surfing over the reef crest.